The Investigation of Effect of Defects on the Structural, Optical, and Magnetic Properties of CuAlO2 - Boyraz, C.; Guler, A.; Karatas, O.; Aksu, P.; Alphan, M. Can; Arda, L. (Polish Acad Sciences Inst Physics, 2022)
Rapid synthesis of delafossite CuAlO2 was achieved by a solid-state reaction method. The synthesized sample was subjected to phase analysis by X-ray diffraction. The desired crystalline phase was obtained and all peaks in the X-ray diffraction phase investigation were found to belong to the CuAlO2 pattern. Morphological and stoichiometric properties were defined by a scanning electron microscope and insitu attachment of energy dispersive spectroscopy. X-ray photoelectron spectroscopy measurements were done to provide a detailed elemental composition analysis in the parts per thousand ranges. X-ray photoelectron spectroscopy measurements revealed that the core level of the 4 electron species Cu 2p, Al 2p, and O 1s exists. The structural defects of CuAlO2 were investigated using the Agilent Cary Eclipse Fluorescence Spectrophotometer. The photoluminescence measurements showed that the near-band emission, cooper vacancy, and oxygen vacancy emission occurred. The nature of optical and magnetic properties of the CuAlO2 sample was defined by Quantum Design Physical Properties Measurement System and correlated with the X-ray photoelectron spectroscopy and photoluminescence results.
Keywords: delafossite CuAlO2; optical and magnetic properties; solid-state reaction method; nanostructures